Tra conservazione e rischio di estinzione: la minoranza etno-linguistisca slovena in Italia - Igor Jelen; Roland Löffler; Peter Čede; Ernst Steinicke (Bollettino della Società Geografica Italiana)
The study analyzes the spatial fragmentation in the Slovenian settlement area in Italy and highlights assimilation and demographic processes that exert influence on the Slovenian-speaking minority. The work builds on the current status of research and is based on official data, their evaluation through qualitative investigations as well as on further results of own research on site. The Slovenian-language population in Friuli Venezia Giulia is currently estimated at about 46,000 people. The main settlement area is the eastern border zone of this region, which is characterized by different cultural and regional identities. While the Slovenian-speaking population of Friuli (Val Canale and Slavia) focuses more on its cultural and regional distinctions, the majority of the Slovenian-language group in Venezia Giulia considers itself a “national minority.” Thus, the overall assessment of the possible future of the Slovenian-language group varies thus from region to region.